2018
DOI: 10.1002/biot.201800253
|View full text |Cite
|
Sign up to set email alerts
|

Rational Engineering ofBacillus cereusLeucine Dehydrogenase Towards α-keto Acid Reduction for Improving Unnatural Amino Acid Production

Abstract: Unnatural amino acids (UAAs) play a key role in modern medicinal chemistry such as small molecules and peptide-based drugs with fast-growing markets. Low efficiency for natural enzymes including leucine dehydrogenase (LeuDH, EC1.4.1.9) are one major challenge for UAA production. Here, rational engineering of LeuDH from Bacillus cereus with a structure-based design approach is studied. The results achieve higher enzymatic activity and stability toward α-keto acid reduction by improving the hydrophobic and rigid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…Then, we introduced NADH-dependent L-leucine dehydrogenase from Bacillus cereus (BcLeuDH) to construct a hydrogen-borrowing dual-enzyme cascade system for catalyzing D-α-HAs to L-UAAs (shown in Figure 1). As in our precious work, we found that BcLeuDH could catalyze not only aromatic substrates but also aliphatic α-keto acids [9,29], which was suitable for this cascade system. Our strategy provided an efficient strategy for biocatalytic preparation of a broad-range L-UAAs, with the enhancement of LbMDH activity towards aromatic and aliphatic α-Has, contributing significantly to the biocatalytic preparation of UAAs.…”
Section: Of 14mentioning
confidence: 61%
See 2 more Smart Citations
“…Then, we introduced NADH-dependent L-leucine dehydrogenase from Bacillus cereus (BcLeuDH) to construct a hydrogen-borrowing dual-enzyme cascade system for catalyzing D-α-HAs to L-UAAs (shown in Figure 1). As in our precious work, we found that BcLeuDH could catalyze not only aromatic substrates but also aliphatic α-keto acids [9,29], which was suitable for this cascade system. Our strategy provided an efficient strategy for biocatalytic preparation of a broad-range L-UAAs, with the enhancement of LbMDH activity towards aromatic and aliphatic α-Has, contributing significantly to the biocatalytic preparation of UAAs.…”
Section: Of 14mentioning
confidence: 61%
“…With the help of structure and sequence analysis, we had a thorough understanding of the conserved active site and substrate channel of LbMDH. In addition, it has been proved that the residues near the active pocket or substrate channel show a significant effect in enzymatic catalytic efficiency and the substrate affinity [9,32]. Thus, six residues (V127, L189, L193, I204, L243, and Q247) near the active pocket or substrate channel were chosen for site-directed mutagenesis (Figure 2B).…”
Section: Rational Engineering Of Lbmdhmentioning
confidence: 99%
See 1 more Smart Citation
“…Leucine dehydrogenase LeuDH, encoded by leuDH , is a NAD(H)-dependent amino acid dehydrogenase, catalyzing the reductive amination of a variety of aliphatic keto-acids to the corresponding l -amino acids [31]. The reaction is reversible using NAD + as a factor (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…LeuDH, which is an amino acid dehydrogenase using NADH as a cofactor, catalyzes the reversible oxidative deamination and reductive amination between l -leucine or other branched chain amino acids and their corresponding α-keto acids [38]. Although various active or artificial amino acids have been synthesized by leucine dehydrogenases in vitro [6,31], the effect of leucine dehydrogenases in biological l -leucine fermentation has not yet been recognized in detail. Nevertheless, the NAD-dependent LeuDH was expected to be effective for l -leucine biosynthesis.…”
Section: Discussionmentioning
confidence: 99%